(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The increase in bacterial resistance and bacterial pathogens are major health problem for the Human around the world. So, to control multidrug resistant bacteria, a hybrid novel heterocyclic molecules 2-chloro-N’-((5-(3-(substituted phenyl)acryloyl)thiophen-2-yl)methylene)nicotinohydrazide (5a-h) and 2-chloro-N’-((5-(5–substitutedphenyl)isoxazol-3-yl)thiophen-2-yl)methylene)nicotinohydrazide (6a-h) are designed and synthesised. Structures of all the prepared compounds are confirmed on the basis of FTIR, 1H NMR, 13C NMR, Mass spectral data as well as elemental analysis. Proficiency of the title compounds as antimicrobial as well as antitubercular are screened against selected pathogens. Some of the newer hybrid molecules showed excellent activity and as a excellent future scope in pharmacological research.